Analisis Tingkat Adopsi Inovasi Petani pada Budidaya Kelengkeng dengan Pemboosteran - Kreshna Awal Yudhistira; Siti Nurlaela; Suharno Suharno (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The cultivation of longan (Dimocarpus longan Lour) has significant economic potential, especially when supported by innovation in flowering induction techniques known as “Booster.” This study aims to analyze the level of innovation adoption among longan farmers in Dusun Timur, Kalurahan Selomartani, Yogyakarta, focusing on booster methods such as root injection, drip bore, and watering with chemical solutions. A qualitative descriptive method was used, involving purposive sampling of key informants including local farmers and agricultural stakeholders. Data were analyzed using SWOT, IFAS-EFAS, and QSPM matrices to identify internal and external factors influencing innovation adoption. However, barriers such as limited knowledge of modern boosters, high costs, and resistance to complex methods (e.g., bore technique) hinder broader adoption. The most influential strategies identified include pest control during fruiting and synchronized flowering scheduling. Overall, the innovation has been widely accepted due to its observable advantages, compatibility with local practices, and low complexity in some methods. Strengthening extension services and local training is essential to sustain and expand this innovation.